Governance for sustainable social enterprise performance: moving beyond control mechanisms / Aziatul Waznah Ghazali ... [et al.] - Ghazali, Aziatul Waznah; Shafie, Nur Aima; Mohd Sanusi, Zuraidah; Sanusi, Soliha; Zolkaflil, Salwa (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
One of the prominent challenges of social enterprises is the inability to sustain their performance. In recent years, there have been instances where social enterprises have faced issues related to mismanagement, and these incidents have been associated with lack of effective governance. Therefore, this qualitative study engaged semi-structured interviews with representatives of social enterprises in Malaysia in assessing and examining the ideal governance framework that would suit the needs of social enterprise to attain sustainable performance. At first glance, the findings suggest that governance is achieved through effective control mechanisms and accountability practices. However, the respondents had also shared some insights that would suggest a forward-looking approach to social enterprise governance that prioritises sustainability, innovation, and social impact, rather than just control and compliance. Additionally, another substance being highlighted by the respondents that is closely related with social enterprise governance is about building relationships and trust.